Preparation and Characterization of a Novel Terbium Complex Coordinated with 10-Undecenoic Acid for UV-Cured Coatings - Chenjie Jiao; Rong Zhong; Yanfang Zhou; Hongfei Zhang (International Journal of Polymer Science)
A UV-cured composite containing a rare earth complex was prepared for this study. First, the photoluminescent terbium complex was synthesized with a long-chain unsaturated fatty acid (10-Undecenoic acid) by a solution precipitation method, resulting in the 10-UA-Tb(III) complex. Its structure was proven by FTIR, elemental analysis, XRD, and TGA. The results indicated that the organic acid ligand successfully coordinated with the Tb3+ ion and that the complex had a chelate bidentate structure. The emission spectrum of the 10-UA-Tb(III) complex indicated that the complex can emit a bright green light with the unique luminescence of the Tb3+ ion. Furthermore, the luminescence properties of complexes with different ratios of Tb3+ and ligand were studied, and the ratio of Tb3+ and the ligand had an obvious impact on the luminescence intensity of the 10-UA-Tb(III) complex. Subsequently, the prepared rare earth complex was doped into a UV-cured coating in different proportions to obtain a UV-cured composite. The morphology of the rare earth UV-cured composite was observed by SEM. The images showed that the rare earth complex was dispersed uniformly in the polymer matrix. Moreover, the composites could emit fluorescence. Additionally, it has good thermal stability and compatibility with the resin. Therefore, these composites should have potential applications in UV curable materials, such as luminescence coatings.